Can Sequential Coagulation Monitoring Predict Major Haemorrhage in Extremely Low Birth Weight Infants? - Thanhaeuser, Margarita; Binder, Christoph; Derhaschnig, Ulla; Jilma, Bernd; Kornsteiner-Krenn, Margit; Huber-Dangl, Mercedes; Repa, Andreas; Kreissl, Alexandra; Berger, Angelika; Haiden, Nadja (Thrombosis and Haemostasis, 2018)
Introduction Bleeds such as intra-ventricular (IVH) and pulmonary haemorrhage (PH) are life-threatening events in extremely low birth weight (ELBW) infants. Serial coagulation monitoring by measuring the international normalized ratio (INR) with small volume samples might facilitate early diagnosis and possibly prevent major bleeds.Materials and Methods This was a prospective longitudinal study performed in ELBW infants, who received serial INR monitoring by point of care testing during their first 30 days of life. The primary objective was to explore whether INR monitoring could predict major bleeding events (IVH, PH). Secondary objectives were mortality and feasibility in this patient population.Results A total of 127 ELBW infants were stratified into a bleeding and a non-bleeding group. Bleeding events occurred in 31% (39/127) of the infants, whereupon 24% developed IVH and 9% PH. Infants in the bleeding group were 4 days younger at birth (p = 0.05) and had a substantially higher mortality rate of 26% versus 5% in controls (p = 0.005). Median INR during the first 3 days before a bleeding event was 1.55 (95% confidence interval [CI]: 1.39–1.74) compared with the control group with 1.45 (95% CI: 1.44–1.58; p = 0.81). Platelet counts were significantly lower in the bleeding group on the 3rd day and during the 2nd to 4th week of life.Discussion Serial coagulation monitoring by an INR point of care testing is feasible in ELBW infants but could not predict bleeding events. Further studies with daily monitoring of INR and platelet counts during the first days of life might be able to more precisely detect a risk of major haemorrhage in ELBW infants.
Keywords: coagulation monitoring; intra-ventricular haemorrhage; pulmonary haemorrhage; premature infant